Analysis of Writing Skill Stages of 5-6 Year Old Children in Learning with the BCCT (Beyond Center and Circle Time) Model - Raihana Chairani; Peny Husna Handayani (Indonesian Journal of Advanced Research, 2024)
The purpose of this study is to describe the level of writing skills of children aged 5-6 years at the stage of crossing out, linear repetition/tracing horizontal writing, writing short writing in learning using the BCCT (Beyond Center and Circle Time) model at TK Negeri Pembina Tanjung Morawa in the 2023/2024 academic year. This study used descriptive qualitative research. This study was conducted with 9 children aged 5-6 years old at TK Negeri Pembina Tanjung Morawa. The data in this study started from data collection, data reduction, data presentation, and drawing conclusions. The results of the study showed that the stages of children's writing skills in learning with the BCCT (Beyond Center and Circle Time) model were at the stages of crossing out, linear repetition, random writing, and writing names. While the other two showed the results of writing skills in learning with the BCCT (Beyond Center and Circle Time) model at the stages of crossing out, linear repetition, random writing.